Improving Ability to Memorize Mufradat Arabic with Snakes and Ladders Game Media in Class IV Elementary School Bustanul Ulum Batu City - Devi Wahyu Ertanti (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2018)
Selection and proper use of media in the learning process can build the student's character and determine the achievement of student learning goals. The ladder snake game media is an innovative media development used to stimulate students' ability to memorize, remember, and understand the learning topics being studied. This study applies an interesting and meaningful learning media for learners, with the application of play based media while learning can stimulate students in memorizing Arabic mufrodat with more fun. This research is a qualitative research with type of PTK which is implemented with several cycles. Data collection techniques used were observation, interview, documentation and test instruments (pre-test and post-test). Result of the research: (1) learning activity was carried out in two cycles, with the result of the students learning on average got 87,2 in cycle II; (2) game media of snake ladder can improve the ability of Arabic mufrodat memorization with student mastery 70,5% in cycle I increase to 88% in cycle II.